ANALISIS PENGARUH PROFESIONALISME TERHADAP TINGKAT MATERIALITAS DALAM PROSES PENGAUDITAN LAPORAN KEUANGAN (Studi Empiris pada Auditor Eksternal di Kota Semarang) - Marfin Sinaga; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2012)
This study aims to determine the relationship between the professionalism of the auditor as an independent variable consisting of the dimensions of dedication, community affiliation, autonomy demand, belief self regulation, social obligation with the dependent variable, namely consideration of the level of materiality in the audit process financial statements. The respondents are a few professionals who work well as part-time jobs, junior auditor, senior auditor, supervisor, manager or partner at public accounting firm located in Semarang. Sampling was done using a type of non-probability sampling, to collect some important information provided by respondents. The questionnaire is a tool used to measure the variables. Analytical model used is multiple linear regression to determine whether there is a relationship between the auditor materiality level of professionalism and consideration in the process of auditing the financial statements. Based on the calculation and analysis conducted shows that there is a positive correlation between variables with a consideration of professionalism auditor materiality levels, including the dedication, the dimension, the dimension of independence, and relationships with other professions. Positive correlation between the independent variables with the dependent variable showed that the higher the professionalism of an auditor will be more appropriate then the auditor's consideration of materiality in auditing financial statements.